Kangaroo Method Care In The Family: A Cross Sectional Study In Makassar City Indonesia - Aslinda, Masni, Veni Hadju, Kadek Ayu Erika, Apik Indarty Moedjiono, Shanti Riskiyanti, Abdul Salam, Nursalam, Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Kangaroo Method Care (KMC) is skin-to-skin contact between the baby and the mother on the chest of the mother or family that has been proven by several studies to be beneficial in improving the physiological function of Low Birth Weight (LBW) Babies, increasing closeness between mother and baby, increasing baby weight, and increasing exclusive breastfeeding. KMC is not only carried out in hospitals, but the continuity of the implementation of this care continues to be carried out at home. The inability of parents to care for babies and the disconnection of care from the hospital to the community causes the baby’s health to not be monitored optimally. Health education and support are needed to increase the responsibility and awareness of mothers to carry out KMC because the role of the family is very important in maintaining the success of kangaroo care methods, but information regarding the description of the implementation of the kangaroo method at home is still limited. Objective : This study aims to see the prevalence of kangaroo care methods, benefits, support and barriers to implementation at home. Methods : This study is an analytical descriptive study with a cross-sectional study approach, sampling with purposive sampling and the number of respondents was 68. Univariate and bivariate analysis using SPSS version 24.0. Univariate analysis was conducted to determine the prevalence of kangaroo care at home, knowledge related to kangaroo care, sources of information, benefits of kangaroo care, obstacles and sources of support received by mothers in implementing kangaroo care at home. Bivariate analysis with the Chi-Squere test to identify the relationship between demographic factors of parents and infants, information related to KMC, sources of support and sources of information related to kangaroo care with the implementation of kangaroo care at home . Results : LBW mothers who practiced kangaroo care at home were 41 (60.3%) with a maximum duration of 1-2 hours a day, the number of respondents was 19 (27.9%). As many as 50 (73.5%) received information related to kangaroo care (KMC) with the most information source from health workers as many as 34 (50%). The sources of support received came from husbands, parents and relatives. The form of support received was physical support, emotional support and information on instructions for implementing kangaroo care. The benefits obtained from implementing kangaroo care are improving the growth and health of low birth weight babies, increasing closeness to the baby and providing comfort to the baby. The obstacles obtained were lack of time, physical discomfort, lack of information, baby condition and difficulty in implementing KMC. There is a relationship between maternal education, maternal occupation, father’s age, support from husband, family and relatives, information related to KMC, and sources of information from the internet and health workers with the implementation of kangaroo care at home with a value of ƿ <0.05. Conclusion: support from husband and parents as well as information related to kangaroo care methods are very necessary to maximize the implementation of kangaroo care methods at home.